Immune-related genes expression analysis of Western mosquitofish (Gambusia affinis) challenged with Aeromonas hydrophila. Issue 102 (July 2020) - Liu, Shulin; Zhou, Aiguo; Xie, Shaolin; Sun, Di; Zhang, Yue; Sun, Zhuolin; Chen, Yanfeng; Zou, Jixing
Abstract: The great Gambusia affinis ( G. affinis ) is considered as an important animal model to study the endocrine disruption, ecological behavior, and environmental pollutant. The present study aims to build a new promising infection model with Aeromonas hydrophila ( A. hydrophila ) in aquaculture. The mRNA expression of Rac1, MyD88, IRAK4, TAK1, IKKβ, and IL-1β in G. affinis were significance higher ( P  < 0.05) in the liver of G. affinis than that of brain and intestine. And the PI3K mRNA expression level was significant lower ( P  < 0.05) in the intestine than that of brain and liver. The mRNA levels of AKT3 were significant higher ( P  < 0.05) in the brain than that of liver and intestine. And then the brain, liver, and intestine were collected at different time points (0 h, 3 h, 9 h, 18 h, 24 h, 48 h) after post injection of LD50 of A. hydrophila . The 0.85% NaCl was used as a negative control for the LD50 of A. hydrophila . The RT-PCR results showed that mRNA expressions of TLR2/4 pathway downstream genes MyD88, IRAK4, TAK1, Rac1, IKKβ, and IL-1β were firstly significantly up-regulated ( P  < 0.05) and were then backed to the 0 h group levels in three tissues. In contrast, mRNA expressions of TLR2/4 pathway downstream genes PI3K and AKT3 were firstly significantly decreased ( P  < 0.05) and were then increased to the 0 h group levels in brain and intestine. In summary, the results indicated that A. hydrophila could cause inflammatory reaction in intestinal and brain. In addition, the liver showed a provocative reaction when infected with A. hydrophila . Highlights: TLR2/4 signaling pathways related genes from Gambusia affinis were identified. Gambusia affinis is sensitive to Aeromonas hydrophila infection through analysis of expression patterns in different tissues. The great Gambusia affinis has the potential to be a model of bacterial infection.